EVALUATION OF ANTIOXIDANT AND ANTIHYPERLIPIDEMIC ACTIVITY OF INDIAN GOOSEBERRY (E mblica officinalis) FRUIT IN HIGH FAT-FED RABBITS - S. Zahid K. M. Anjum; M. S. Mughal; A. Yaqub; M. Yameen (Journal of Animal and Plant Sciences, 2018)
Hyperlipidaemia leads to various diseases including cardiovascular and diabetes mellitus, etc. Among the many reasons for the abnormal lipid profile, high fat intake and sedentary life style are the main reasons for hypercholesterolemia. In the present study, a total of 25 (n=25) rabbits were used and were randomly divided into five groups which received different treatments. Group I served as control, group II received a measured quantity of Emblica officinalis (EO) powder, group III received high fat diet ( HFD), group IV received HFD and EO powder and group V received HFD and the standard drug atorvastatin for eight weeks. To investigate the effects of EO powder, blood and tissue (liver and kidney) samples were taken at the end of the eight weeks of experimentation and serum was evaluated for various blood plasma lipid parameters and antioxidant enzymes of liver and kidney. There was a significant increase in all the lipid parameters except for HDL in the group of rabbits receiving HFD; HDL level decreased significantly (P< 0.05) . High fat intake may have resulted in the production of free radicals which created an oxidative stress and lipid peroxidation ultimately leading to abnormal lipid profile. Antioxidant enzymes, such as Superoxide dismutase ( SOD), Catalase (CAT) and Glutathione ( GSH) were significantly reduced in the HFD group indicating clearly that high fat diet leads to oxidative stress. Emblica officinalis relieved the oxidative stress of liver and kidney tissues in group IV indicating that EO powder has the potential to inhibit the oxidative stress and lipid peroxidation because of poly-phenols, flavonoids, ascorbic acid and other chemicals present in it. Further, it is concluded that although statins are useful in reducing blood plasma lipid profile, they simultaneously have many side effects. The findings of the present study reveal that EO powder is useful in reducing hyperlipidaemia and tissue damage. frequently used to avoid damages of hyperlipidaemia.
Keywords: Emblica officinalis; Atorvastatin; Hyperlipidemia; Lipid Profile; Medicinal Plants.